2013
DOI: 10.1002/ejic.201301017
|View full text |Cite
|
Sign up to set email alerts
|

Noncovalent Chalcogen Bonds and Disulfide Conformational Change in the Cystamine‐Based Hybrid Perovskite [H3N(CH2)2SS(CH2)2NH3]PbIII4

Abstract: International audienceThe cystamine-based hybrid perovskite, α-[NH3(CH2)2S-S(CH2)2NH3]PbI4 (1a), can be transformed into its polymorph, β-[NH3(CH2)2S-S(CH2)2NH3]PbI4 (1b), by heat activation (T = 150 °C). The crystal structures have been characterised by single-crystal X-ray diffraction, whereas the phase transition was followed by both solid-state 1H,13C cross-polarisation magic-angle spinning (CPMAS) NMR spectroscopy and thermodiffractometry techniques. At 150 °C, compound 1a is transformed into 1b, and, rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 94 publications
0
7
0
Order By: Relevance
“…The structures of (MEA) 2 PbI 4 and (PDSBA)PbI 4 are firstly reported in this study (Figure 2a, S1, and S3). As for (DSBA)PbI , Louvain et al reported two polymorphs 22 and in this study we only synthesized the one with α-conformation which is believed to be more stable at room temperature. We noticed that the use of the reductant hypophosphorous acid (H 3 PO 2 ) is the key to the synthesis of (MEA) 2 PbI 4 to avoid the undesired, spontaneous oxidation of MEA (see Experimental Section).…”
Section: Resultsmentioning
confidence: 99%
“…The structures of (MEA) 2 PbI 4 and (PDSBA)PbI 4 are firstly reported in this study (Figure 2a, S1, and S3). As for (DSBA)PbI , Louvain et al reported two polymorphs 22 and in this study we only synthesized the one with α-conformation which is believed to be more stable at room temperature. We noticed that the use of the reductant hypophosphorous acid (H 3 PO 2 ) is the key to the synthesis of (MEA) 2 PbI 4 to avoid the undesired, spontaneous oxidation of MEA (see Experimental Section).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the difference apparent in unit-cell metrics and space group compared with the chloride, the resulting layer topology is actually very similar: this time the tilt mode is disallowed, rather than just very small. In contrast, the iodide exists in two polymorphs which co-exist over a wide temperature range (Louvain et al, 2014). The high-temperature -phase has the common a À a À c, P2 1 /a structure (724583) with disordered cystamine moieties, whereas the ambient-temperaturephase has a more complex supercell discussed in Section 3.3.…”
Section: More Complex Derivativesmentioning
confidence: 99%
“…Note that there is a significant change in the inorganic layer from to , with a change of rotation mode from c to (Àc), in addition to the changes in the conformation and positioning of the cystamine. Although the tilt system and layer shift in thephase result in a similar overall structure to that of the chloride and bromide, the expanded superlattice is caused by ordering of two distinct enantiomeric forms of the cystamine: all these interesting features are discussed in more detail by Louvain et al (2014) For n-butylamine a more diverse range of phases has been reported, which are discussed in Section 4.2.…”
Section: More Complex Derivativesmentioning
confidence: 99%
“…2 Therefore, the preparation of 3D semiconductor crystals is fundamental and is being intensively researched. [3][4][5] Inspired by 3D supramolecular assembly 6 of biological molecules such as DNA, peptides and nacre in solution system, 7,8 supramolecular assembly technology extends to the preparation of 3D inorganic/organic semiconductor crystals. 9,10 However, the 3D assembly of p-conjugated polymer crystals is still a challenge because 3D fantastic self-assembly requires coded nanocrystals 11 with a sufficiently monodisperse distribution of size and shape first, then these nanocrystals repeat the ''bottomup'' self-assembly into 3D crystal structure along the optimal dynamic path, these configurations may be affected by a considerable number of energy contributions (for example, p-p stacking interaction, van der Waals, electrostatic, and dipolar), as well.…”
mentioning
confidence: 99%